Mao. 10 - Takahashi, Rumiko, 1957- (Shōnen Sandē komikkusu., 2023)
"Exorcise your destiny in an era-spanning supernatural adventure from manga legend Rumiko Takahashi! When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! When Yurako reveals the history of her relationship with Mao, Nanoka starts to question her own feelings for him. But she doesn't have much time to dwell on her romantic life before the gang is off to investigate mysterious cases of spontaneous human combustion! Who is behind the immolation of wealthy local bureaucrats? Plus, the tragic story of Hyakka's arrival at the Goko clan's dojo. And finally, Shiranui and Hakubi's master plan is revealed!" --